Dissemination strategies: experience and lessons learned. (30th September 2020) - Arwidson, P; Verry-Jolivet, C
Abstract: The French national public health agency is building a portal of evidence-based and promising interventions. The aim of this project is to improve the effectiveness and the efficiency of public health interventions. The portal currently contains around 80 descriptive files. But this portal is only part of a system. Each decision maker or project manager interested in an intervention must be able to have access to qualified trainers, to manual and have assistance in quality assessment. It is also necessary to adapt the interventions to each local context without losing the effectiveness demonstrated in the evaluation or initial research. It is essential to document all the local adaptations in a centralized information system and to compare them with a fidelity measure or a monitoring tool. David Chambers has named this type of system an Adaptome (AJPM 2016; 51: S124-S131). Several programs, adapted from international programs (Strengthening families' program, Good behavior game, nurse family partnership), or based on French research (Tabado, ICAPS), are being deployed. The challenges and difficulties of these deployments will be discussed.